Patient-centered perspectives on perioperative care - Saasouh, Wael; Ghanem, Kristina; Al-Saidi, Neil; LeQuia, Lindsey; McKelvey, George; Jaffar, Muhammad (Frontiers in Anesthesiology, 2024)
Patient-centered care describes the process in which patients are actively involved in the creation of their care plan with their healthcare providers. By allowing patients to be active participants in their own health, care plans can be personalized to optimize outcomes. However, not all patient-provider interactions allow patients to voice their opinions regarding their experience. Patient surveying systems present an opportunity to provide feedback about healthcare experiences so that providers and institutions can enact changes and advance towards a more patient-centered environment. Oftentimes these surveys can take weeks to be distributed, creating a lag between the identification of a negative factor and advancement of the healthcare environment. Implementing random-domain intercept technology (RDIT), as described in this study, provides a novel opportunity for patients to actively participate in improving healthcare systems through the submission of real-time responses. Unique to RDIT, these surveys are distributed electronically and across geographical barriers which allows for real-time feedback to be retrieved and leads to increased generalizability for changes across healthcare systems. The novel use of RDIT lays the groundwork for a dynamic healthcare environment that can swiftly respond and evolve towards better relevant outcomes.